Respuesta :

Your equation is: 

f(x) = 7x - 2 

Solve for x. 

Add 2 to both sides of this equation to get: 

f(x) + 2 = 7x 

Divide both sides of this equation by 7 to get: 

(f(x) + 2)/7 = x 

Since, in general, a = b implies that b = a, this equation becomes: 

x = (f(x) + 2)/7 

Replace x with f(x) and replace f(x) with x to get: 

f(x) = (x+2)/7 

That's your inverse function. 

Graph both your function and your inverse function. 

Set y = f(x) to get: 

y = 7x - 2 (your regular function). 

y = (x+2)/7 (your inverse function). 

Graph also the function y = x. 
just follow the steps you will have the idea
Ver imagen Caprice26
ACCESS MORE